The Influence of Management Control Systems on Employee Performance from an Islamic Perspective - Aprilia, Helda; Hanif, Hanif; Ermawati, Liya; Pramasha, Raizky Rienaldy (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
The management control system is important to support the optimal performance of a company. This is because the management control system plays a role in controlling individual behavior in the company. There are several factors that influence the management control system, namely external and internal factors. The research method used in this research is quantitative research with the research object being 33 employees of PT United Tractors Tbk Lampung branch. The type of data used is primary data obtained from distributing questionnaires to 28 research samples using purposive sampling technique. The data analysis used is simple linear regression analysis using the SPSS 25 program. The research results show that the management control system has a positive and significant effect on employee performance. Whereas in the Islamic perspective, it encourages a person to pay attention to what he is doing as stated in surah Al-Hasyr verse 18.